2010
DOI: 10.1103/physrevd.82.103508
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of clumpy dark matter in the global 21 cm background signal

Abstract: We examine the extent to which the self-annihilation of supersymmetric neutralino dark matter, as well as light dark matter, influences the rate of heating, ionisation and Lyman-α pumping of interstellar hydrogen and helium and the extent to which this is manifested in the 21 cm global background signal. We fully consider the enhancements to the annihilation rate from DM halos and substructures within them. We find that the influence of such structures can result in significant changes in the differential brig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(85 citation statements)
references
References 141 publications
3
81
1
Order By: Relevance
“…This is appropriate at high redshift, when density fluctuations are small and perturbative, and conservative in all cases; it allows a very robust and precise constraint, since the cosmological density of the DM is constrained at the percent level. However, there has been considerable interest in the effects of DM annihilation/decay at lower redshifts (z 30) where there might be measurable effects on the 21 cm line of hydrogen [17][18][19][20][21][22], or where the annihilation byproducts might help reionize the universe [23][24][25][26][27].…”
Section: Inclusion Of Structure Formationmentioning
confidence: 99%
“…This is appropriate at high redshift, when density fluctuations are small and perturbative, and conservative in all cases; it allows a very robust and precise constraint, since the cosmological density of the DM is constrained at the percent level. However, there has been considerable interest in the effects of DM annihilation/decay at lower redshifts (z 30) where there might be measurable effects on the 21 cm line of hydrogen [17][18][19][20][21][22], or where the annihilation byproducts might help reionize the universe [23][24][25][26][27].…”
Section: Inclusion Of Structure Formationmentioning
confidence: 99%
“…1 in Ref. [15]). For DM halo mass 10 6 M ⊙ , the differences of ∼ 5 orders of magnitude differences are present at z ∼ 20 compared with the DM smooth distribution.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the Ref. [15], the authors discussed the effects on the 'boost factor' for the different values of the smallest DM halos. They found that there are differences of ∼ 2 orders of magnitude of the 'boost factor' for DM halo mass 10 −12 M ⊙ and 10 −4 M ⊙ at z ∼ 50 (upper panel of Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations